2020
DOI: 10.1111/pce.13928
|View full text |Cite
|
Sign up to set email alerts
|

Root exudates drive soil‐microbe‐nutrient feedbacks in response to plant growth

Abstract: Although interactions between plants and microbes at the plant–soil interface are known to be important for plant nutrient acquisition, relatively little is known about how root exudates contribute to nutrient exchange over the course of plant development. In this study, root exudates from slow‐ and fast‐growing stages of Arabidopsis thaliana plants were collected, chemically analysed and then applied to a sandy nutrient‐depleted soil. We then tracked the impacts of these exudates on soil bacterial communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(103 citation statements)
references
References 65 publications
(80 reference statements)
6
77
0
Order By: Relevance
“…Our results also showed that plant developmental stage had signi cant effects on the rhizosphere and bulk soil microbiomes, though it was much weaker than the site effects, implying that plants also have profound in uence on soil microbiomes via strong rhizosphere effect [6,35,74]. Collectively, by examining the temporal dynamics of bacterial and fungal microbiomes in the soil-plant continuum of maize and fake plants phylloplane in geographically distant sites, this study considerably expanded our knowledge on the succession of plant microbiomes and their potential function under different temporal and spatial scales in eld.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our results also showed that plant developmental stage had signi cant effects on the rhizosphere and bulk soil microbiomes, though it was much weaker than the site effects, implying that plants also have profound in uence on soil microbiomes via strong rhizosphere effect [6,35,74]. Collectively, by examining the temporal dynamics of bacterial and fungal microbiomes in the soil-plant continuum of maize and fake plants phylloplane in geographically distant sites, this study considerably expanded our knowledge on the succession of plant microbiomes and their potential function under different temporal and spatial scales in eld.…”
Section: Discussionsupporting
confidence: 52%
“…For example, it was suggested that rice root microbiota varied dramatically during the vegetative stages but stabilized after reproduction [33]. This is expected given that plant physiological requirement and composition of plant exudates vary with its developmental stages [9,13,34,35]. However, we lack empirical evidence for underpinning the mechanisms of microbiome assembly across soil, plant epiphytic and endophytic niches along with plant developmental stage in eld under the interactive in uence of climate, edaphic factors and fertilization regimes.…”
Section: Introductionmentioning
confidence: 96%
“…Naturally, the adaptive evolution and composition of microbial communities are governed by plant species, developmental stages, and environmental factors ( Ma et al, 2016 ). Rhizosphere microorganisms, especially beneficial bacteria and fungi, co-evolve with their host to adjust the community structure based on the specific environments, ultimately improving plant performance and enhancing plant resistance to stress conditions both directly and indirectly ( Grover et al, 2011 ; Zhao et al, 2021 ). For example, Li X. et al (2016) found that mulberry-soybean intercropping increases the abundance of beneficial bacteria (phosphate-solubilizing bacteria) in intercropping samples under salt-alkali soil condition.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum diversity in exudate compositions has been generally found during maximum vegetative growth; this was also related to maximum expression of bacterial genes related to nutrient (N and P composes) acquisition. Changes in exudation pathways during different plant growth stages are therefore essential for recruiting bacterial populations which can support plant growth [119]. Plant and rhizobacteria genomes, strictly linked in a coevolutionary process, can be defined as a hologenome [104,116].…”
Section: Heavy Metals and Secondary Metabolitesmentioning
confidence: 99%
“…However, in many cases, the molecular structure of these compounds is still not known [ 16 , 111 ]. For example, in the plant Arabidopsis thaliana , more than 500 compounds have been detected at different growth stages [ 119 ] and with a natural intraspecific variability [ 118 ]. Zhalnina et al [ 116 ] found that different growth stages of Avena barbata were characterized by different exudate compositions.…”
Section: Plant–bacteria Interactions In Rhizosphere and Defense From Heavy Metal Stressmentioning
confidence: 99%